Englisches im Gegenwartsdeutschen der Touristikbranche - Kowalonek-Janczarek, Monika; Pola, (Glottodidactica, 2015)
The influence of English on German has grown in the last decades and is likely to continue. The aim of this paper is to investigate the occurrence of Anglicisms in the travel magazine Lonely Planet Traveller Deutschland (October, 2014). The particular focus is on the parts of speech and word formation types they represent. First we make an attempt to define the terms loanword and Anglicism. In the second part we present and discuss the results of our corpus linguistic study. The findings of the study show the dominance of nouns in the analysed Anglicisms (especially hybrid nominal compounds). The research can be of significance for further studies on the language of tourism industry.